FPGA Implementation of Emergency Door Car Entry System - Zaini Sulaiman (Universiti Malaysia Perlis (UniMAP), 2008)
Emergency door car entry system can be implemented using Field Programmable Gate Array (FPGA) board. FPGA board is a board that can be programmed using source code to run the application that has been downloaded into it. The commonly used board is the Altera® UP2 Education Kit. This kit contains everything that is needed to create a complete system-on-a-programmable-chip (SOPC) solution. Onboard chips are MAX® EPM7128S and FLEX® 10K EPF10K70-240. ByteBlaster™ II Download Cable is the cable used to interface the board to computer’s printer (LPT1) port. Microsoft® Corporation Windows® XP Professional Service Pack 2 is used as the operating system that supports the FPGA board. Different types of source codes can be implemented to the board. Widely used are VHSIC Hardware Description Language (VHDL) and Verilog. VHSIC is an acronym for Very High-Speed Integrated Circuits. VHDL can be used to model a digital system at many levels of abstraction ranging from the algorithmic level to the gate level. Verilog is of the same goal, but it is written using a different format. Verilog is chosen as the source code’s format for the keyless auto entry system. Altera® Quartus II is used to create the source code and download it into the FPGA board. Simulation is done using Simulator Tool in Altera ® Quartus II software. Emergency door car entry system is an access control system, using minimal human effort to have the access. Standard pushbuttons are used as input method and the access depends only on the input timing. These rules are used to write the source code. Although the outputs are represented using light emitting diodes (LEDs), the result and performance is correct. Access can only be reached when the entered password is correct.